1ST Piece =======> 2x ======> 2 * 3 ft. ======> 6 ft.
2ND =========> 5x =======> 5 * 3 ft. ======> 15 ft.
3RD ==========> 4 Feet =======> 4 ft.
Sum ======> 25 Feet
Equation:
(2x + 5x) + (4) = 25
Let's solve your equation step-by-step.
2x + 5x + 4 = 25
Step 1: Simplify both sides of the equation.
2x + 5x + 4 = 25
(2x + 5x) + (4) = 25 (Combine Like Terms)
7x + 4 = 25
7x + 4 = 25
Step 2: Subtract 4 from both sides.
7x + 4 − 4 = 25 − 4
7x = 21
Step 3: Divide both sides by 7.
7x / 7 = 21 / 7
Answer ========> x = 3
Check:
(2x + 5x) + (4) = 25
2(3) = 6
5(3) = 15
3rd Piece = 4
Sum = 25
6ft. + 15ft. + 4ft = 25
25 = 25
Hope that helps!!!!!!!!!!!!! : )